Karakteristik Durasi Konsonan Linguopalatal Bahasa Indonesia sebagai Nilai Dasar Obyektif dalam Evaluasi Kejelasan Ucapan - Suzan Elias (Faculty of Dentistry, Universitas Indonesia, 2015)
An observational research was done to find out the standard value, that could be used in a further research in phonetic problems. The descriptive study was done in 400 respondents, and the correlation with gender, education backgroud and ethnic group. An objective standard value of the duration of linguopalatal consonant bahasa Indonesia which was found in this research used a computer program CSL-50. One of the problems mostly faced in prosthodontic was difficulties in pronouncing linguopalatal consonants by upper removable partial denture wearers with palatal plate.